Patients' use and views of real‐time feedback technology in general practice. (28th April 2016) - Wright, Christine; Davey, Antoinette; Elmore, Natasha; Carter, Mary; Mounce, Luke; Wilson, Ed; Burt, Jenni; Roland, Martin; Campbell, John
Abstract: Background: There is growing interest in real‐time feedback (RTF), which involves collecting and summarizing information about patient experience at the point of care with the aim of informing service improvement. Objective: To investigate the feasibility and acceptability of RTF in UK general practice. Design: Exploratory randomized trial. Setting/Participants: Ten general practices in south‐west England and Cambridgeshire. All patients attending surgeries were eligible to provide RTF. Intervention: Touch screens were installed in waiting areas for 12 weeks with practice staff responsible for encouraging patients to provide RTF. All practices received fortnightly feedback summaries. Four teams attended a facilitated reflection session. Outcomes: RTF 'response rates' among consulting patients were estimated, and the representativeness of touch screen users were assessed. The frequency of staff–patient interactions about RTF (direct observation) and patient views of RTF (exit survey) were summarized. Associated costs were collated. Results: About 2.5% consulting patients provided RTF (range 0.7–8.0% across practices), representing a mean of 194 responses per practice. Patients aged above 65 were under‐represented among touch screen users. Receptionists rarely encouraged RTF but, when this did occur, 60% patients participated. Patients were largely positive about RTF but identified some barriers. Costs per practice for the twelve‐week period ranged from £1125 (unfacilitated team‐level feedback) to £1887 (facilitated team ± practitioner‐level feedback). The main cost was the provision of touch screens. Conclusions: Response rates for RTF were lower than those of other survey modes, although the numbers of patients providing feedback to each practice were comparable to those achieved in the English national GP patient survey. More patients might engage with RTF if the opportunity were consistently highlighted to them.